Working Capital Management: An Antecedent of Successful Supply Chain Management - Roespinoedji, Djoko; Komariah, Siti; Borshalina, Tita; Fati, Meryem; ., Budiman (International Journal of Supply Chain Management, 2019)
The prime objective of current study is to investigate the impact of working capital management tools such as cash conversion cycle, inventory management, and receivable management on the performance of supply chain of manufacturing firms operating in Indonesia. In addition to that, the current study is also interested in examining the moderating role of corporate cash holdings in the relationship between cash conversion cycle and firm supply performance, inventory management and firm supply performance, and receivable management and firm supply performance. To achieve the objective of the current study, we have employed the structural equation modeling and used the statistical package of smart PLS-3. The data by mean of an adapted survey instrument in the form of questionnaire is collected from the operation and finance managers of Indonesian manufacturing firms. International Journal of Supply Chain ManagementThe results of the current study are providing support to the hypothesized results as working capital management appears in significant relationship with firm supply performance. The corporate cash holdings also appear in significant relationship with firm supply performance. The corporate cash holding also appears as a significant moderator between working capital and firm supply performance. The current study which in author knowledge is among few pioneering studies on this issue, will be helpful for financial experts, operation managers, academicians, researchers and other policy makers in formulating policies.